2021
DOI: 10.3390/membranes11060379
|View full text |Cite
|
Sign up to set email alerts
|

Self-Discharge of a Proton Exchange Membrane Electrolyzer: Investigation for Modeling Purposes

Abstract: The self-discharge phenomenon results in a decrease of the open-circuit voltage (OCV), which occurs when an electrochemical device is disconnected from the power source. Although the self-discharge phenomenon has widely been investigated for energy storage devices such as batteries and supercapacitors, no previous works have been reported in the literature about this phenomenon for electrolyzers. For this reason, this work is mainly focused on investigating the self-discharge voltage that occurs in a proton ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…This large voltage range is observed mainly for scenarios relying on falling step currents, where the final value is equal to 0 A. As demonstrated in a previous paper [21], for this specific operating condition at 0 A, the cell voltage converges to 0 V due to the decrease in the open-circuit cell voltage. During the experiments, the variation in the temperature leads to a change in the cell voltage of the PEM electrolyzer, which gathers the reversible voltage, activation, and ohmic overvoltage [22].…”
Section: Discussionmentioning
confidence: 50%
“…This large voltage range is observed mainly for scenarios relying on falling step currents, where the final value is equal to 0 A. As demonstrated in a previous paper [21], for this specific operating condition at 0 A, the cell voltage converges to 0 V due to the decrease in the open-circuit cell voltage. During the experiments, the variation in the temperature leads to a change in the cell voltage of the PEM electrolyzer, which gathers the reversible voltage, activation, and ohmic overvoltage [22].…”
Section: Discussionmentioning
confidence: 50%
“…Besides, in [52], a first value of the capacitance has been provided, equal to 15 mF. This value is much lower than those reported for PEM electrolyzers [53]. Indeed, for PEM electrolyzers, capacitance values from 3 to 69 F have been reported according to the operating conditions.…”
Section: B Electrolytesmentioning
confidence: 78%
“…Most of the published papers investigated PEM electrolyzers [12,[14][15][16] which confirms the growing interest in this technology to generate hydrogen from RES. Moreover, all the published papers reported experiments performed on electrolyzers that demonstrate the relevance of the papers and the significance of using experimental data for investigation purposes.…”
mentioning
confidence: 70%
“…As a result of this Special Issue proposal, five research papers [12][13][14][15][16] from four different countries have been published. Researchers at academic institutions and the French National Centre for Scientific Research (CNRS) from France [12,13,15], Mexico [15], Germany [14], and Taiwan [16] contributed to this work. It is important to point out that the research reported in Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation